CD8+ T-cell exhaustion in cancer: mechanisms and new area for cancer immunotherapy. (15th March 2018) - He, Qi-Feng; Xu, Yong; Li, Jun; Huang, Zheng-Ming; Li, Xiu-Hui; Wang, Xiaochen
Abstract: Immunotherapies have emerged as the most promising area in cancer treatments in recent years. CD8 + T cells, as one of the primary effector cells of anticancer immunity, however, when infiltrating in cancer tissues, are generally in dysfunctional states termed T-cell exhaustion. Exhausted CD8 + T cells are characterized by impaired activity and proliferative ability, increased apoptotic rate and reduced production of effector cytokines. Such dysfunctional CD8 + T cells serve as a barrier in successful cancer elimination. Investigation on the mechanism of T-cell exhaustion was aiming to sustain or restore the efficiency of CD8 + T cells infiltrating in cancer, which may help to develop novel strategies to overcome cancer. Recent studies have found several vital mechanisms of CD8 + T-cell exhaustion and provided novel avenues through targeting CD8 + T-cell exhaustion to enhance anticancer immunity. Here, we review the recent progress in the study of CD8 + T-cell exhaustion to make a summary and to provide a framework for further researches.